PENGARUH KEBIASAAN BERPIKIR TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI BANGUN DATAR KELAS III - Dewi Sinta; Mariyam; Buyung (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
This study aims: (1) To describe students' thinking habits on the material of flat shapes of grade III of Singkawang State Elementary School 25. (2) To describe students' mathematical problem-solving abilities on the material of flat shapes of grade III of Singkawang State Elementary School 25. (3) To determine whether or not there is an influence of thinking habits on students' mathematical problem-solving abilities on the material of flat shapes of grade III of Singkawang State Elementary School 25. The type of research used is quantitative research, with a simple regression approach. Data collection techniques used in this study were non-test and test techniques. The data analysis techniques used were average analysis, percentage and simple regression. The results of the study showed that: (1) Students' thinking habits are classified as very high with an average score of 87. (2) Students' mathematical problem-solving abilities on flat shapes are classified as high with an average of 78. (3) There is an influence of thinking habits on students' mathematical problem solving abilities on the material of flat shapes in class III of Singkawang 25 Elementary School with a positive category.